Endhorpin Massage with Lavender Oil By husband to Increase Breastmilk Production in Breastfeeding Mother in Malang Regency - Rohmah, Miftakhur; Mufida, Riza Tsalatsatul; Ningsih, Dewi Andariya; Hudawati, Nurul (Jurnal Midpro, 2022)
Mother's Milk (ASI) is a liquid milk secretion from the breast after the mother gives birth which is very beneficial for the baby. However, the production of breast milk is a bit of an obstacle in breastfeeding. Giving massage to mothers that can increase endorphins is expected to increase breast milk production. The purpose of the study was to determine the effect of endorphin massage using lavender oil by husbands on increasing breast milk production in breastfeeding mothers in Malang Regency.The design used is Pre Experiment by using a design (One Group Pretest Posttest). A sample of 30 respondents was taken by purposive sampling method. Collecting data using interview and observation techniques, test data analysis using the Wilcoxon test. The results showed that those who had smooth breast milk production after endorphin massage were 21 subjects (70%) and 6 subjects (20%) had sufficient milk production and 3 subjects (10%). The results of the analysis using the Wilcoxon test obtained the results of = 0.000, which means that there is an effect of giving endorphin back massage using lavender oil by the husband on increasing breast milk production in nursing mothers. With that, the husband's back massage endorphin technique can be used as an alternative to increase milk production.